Analysis Of Accounting Information Usage On MSME’s In Central Maluku - Anakotta, Fanny M; Putuhena, Hempry (Politeknik Ganesha Medan, 2024)
The development of MSMEs has become rapid along with the development of the national economy. A deep understanding of accounting is expected to enable the use accounting information for decision-making. This study aims to see the effect of accounting knowledge, business experience, business scale, and owner perception on the use of accounting information. The population and sample in this study are MSMEs in Central Maluku Regency. There are 150 respondent data processed using the SPSS application. The results show that accounting knowledge, business experience, business scale, and owner perception affect the use of accounting information. This research only uses two regencies in Maluku province, expecting that further research will cover the province as a whole Keywords: Accounting Knowledge; Business Experience; Business Scale; Owner Perception; Accounting Information